DIAGNOSING OCULAR MALINGERING IN CHILDREN WITH SIMPLE TEST: IS IT POSSIBLE? Poster Presentation - Case Report - Resident - KEVIN ANGGAKUSUMA HENDRAWAN; NI MADE AYU SURASMIATI; I WAYAN EKA SUTYAWAN; ANAK AGUNG DEWI ADNYA SWARI; MADE KUSUMA WARDANI (Majalah Oftalmologi Indonesia, 2023)
Introduction : Malingering is a condition in children which need a thorough and meticulous examination to diagnose the condition. According to several publication, simple test can be done to diagnose this condition without necessarily performing imaging and electrophysiologic tests. Case Illustration : An 8-year-old male patient, came to eye clinic with sudden visual loss on both eyes for the last 3 days, following pain on both eyes and headache which fluctuating over the last 3 weeks. Patient insisted on wearing black glasses during examinations. Preliminary examination revealed visual acuity no light perception on both eyes. Slit lamp examination and pupillary reflex were normal, fundus examination revealed normal fundus. We tried to do surprise test by suddenly swaying hand towards patient’s eyes and record a visual response. Afterwards we asked patient’s parent to wait outside while performing LEA test which revealed visual acuity 6/6 on both eyes. Further history taking revealed that patient got bullied on school that makes him try to avoid attending school. Discussion : Patient with malingering usually come with decreased vision but seldomly come with blindness. Though it was quite challenging, doing some simple test available in daily practice such as surprise test can help us to diagnose the suspicion. Handling such patient needs a cautious analysis towards patient’s condition and gentle approach towards the patient. It is crucial to rule out organic condition before diagnosing patient with malingering. Conclusion : Simple test such as surprise test can be done in assisting malingering diagnosis when carefully done with the support of thorough history taking and physical